(untitled) (Journal of Health, Technology and Science (JHTS), 2026)
The rising prevalence of metabolic disorders among university students, driven by high-sugar dietary patterns, necessitates functional food interventions. Purple sweet potato (Ipomoea batatas L.) is a carbohydrate source rich in anthocyanins and fiber, potentially modulating postprandial glycemic responses. Objective: This study aims to evaluate the effect of steamed purple sweet potato consumption on blood glucose levels among students of the Nutrition Study Program at Bina Mandiri University, Gorontalo. Method: An analytical experimental study was conducted using a one-group pretest-posttest design involving 35 respondents selected through purposeful sampling. Blood glucose was measured at baseline (fasting) and 120 minutes post-intervention (100g steamed purple sweet potato). Data were analyzed using univariate and non-parametric Wilcoxon Signed Rank tests due to non-normal data distribution. Results: The mean blood glucose increased from a baseline of 122.06 mg/dL to 137.40 mg/dL post-intervention. Statistical analysis yielded a p-value < .001, indicating a significant physiological effect. Although 31.4% of respondents shifted into the pre-diabetic range, the overall mean remained within normoglycemic limits (<140 mg/dL). Conclusion: Steamed purple sweet potato significantly influences blood glucose levels, serving as a controlled carbohydrate source. Its high anthocyanin and fiber content moderate glucose absorption, making it a viable functional food for maintaining metabolic health in young adults with stable insulin sensitivity.